2016
DOI: 10.1038/srep35827
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic oligonucleotide antigens modified with locked nucleic acids detect disease specific antibodies

Abstract: New techniques to detect and quantify antibodies to nucleic acids would provide a significant advance over current methods, which often lack specificity. We investigate the potential of novel antigens containing locked nucleic acids (LNAs) as targets for antibodies. Particularly, employing molecular dynamics we predict optimal nucleotide composition for targeting DNA-binding antibodies. As a proof of concept, we address a problem of detecting anti-DNA antibodies that are characteristic of systemic lupus erythe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…In a good agreement with our recent study 9 , CTD showed a high number of false positive results in healthy controls (31%), which points on non-specific interactions.…”
Section: Resultssupporting
confidence: 92%
“…In a good agreement with our recent study 9 , CTD showed a high number of false positive results in healthy controls (31%), which points on non-specific interactions.…”
Section: Resultssupporting
confidence: 92%
“…We have shown the unique specificity and sensitivity of synthetic DNA oligonucleotides containing locked nucleic acids (LNA) for recognition by monoclonal a-dsDNAs 22 . Recently, other investigators explored rationally designed peptoid antigens for SLE diagnostics 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The graphene layers with deposited amino acids were neutralized in water using NaCl by assuming the height of the simulation box equal to 45Å. The protocol was largely adopted from earlier MD simulation on similar systems [17][18][19]. Particle mesh Ewald method was used to treat the long-range electrostatics [20,21] with a cutoff distance of 12Å.…”
Section: Classical Molecular Dynamics Simulationsmentioning
confidence: 99%